Keystone Flap for Coverage of Large Thoracic Defects: Case Report - Diaz-Chaker, William (2025)
The Keystone island flap is a reconstructive surgical technique used to close large defects in the head, limbs, and trunk. It allows the use of adjacent skin with an excellent color match, reduces operative time, and avoids more complex procedures such as free flaps or grafts. This article describes the use of the Keystone flap in chest wall reconstruction, emphasizing its versatility due to multiple musculocutaneous perforators. It aims to provide plastic surgeons with confidence and flexibility in covering large thoracic soft tissue defects, thereby achieving safe and aesthetically acceptable results. Recommendations and lessons on its use are provided, demonstrating its adaptability to various defect types, ranging from oncological to traumatic lesions, and reducing postoperative mortality while promoting faster recovery.